2013
DOI: 10.1007/s00280-013-2115-z
|View full text |Cite
|
Sign up to set email alerts
|

A preclinical study on the protective effect of melatonin against methotrexate-induced small intestinal damage: effect mediated by attenuation of nitrosative stress, protein tyrosine nitration, and PARP activation

Abstract: Because of its versatility in protecting against nitro-oxidative stress and reducing inflammation, we suggest that melatonin could be beneficial in ameliorating MTX-induced enteritis in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 37 publications
1
30
1
Order By: Relevance
“…Additionally, our map indicates a clear link between MTX and dysbiosis, which to date has not been explicitly unrevealed, although enterocolitis is a known toxic effect of MTX, linked to the induced nitroxidative stress (Kolli et al, 2008, 2013). This is a critical fact as the known adverse effects of MTX, generally described as immunodepressive, appear to be composed not only by the known oxidative organ stress, but also by an added dysbiosis, possibly mediated by an overload on STAT3.…”
Section: Resultsmentioning
confidence: 72%
“…Additionally, our map indicates a clear link between MTX and dysbiosis, which to date has not been explicitly unrevealed, although enterocolitis is a known toxic effect of MTX, linked to the induced nitroxidative stress (Kolli et al, 2008, 2013). This is a critical fact as the known adverse effects of MTX, generally described as immunodepressive, appear to be composed not only by the known oxidative organ stress, but also by an added dysbiosis, possibly mediated by an overload on STAT3.…”
Section: Resultsmentioning
confidence: 72%
“…Interventions that reduce oxidative stress produce beneficial effects in animal models of colitis, suggesting a potential application of antioxidant agents in IBD. Moreover, the demonstrated protective effects of melatonin in murine models of colitis are associated frequently with a reduction of the oxidative stress . Because melatonin is able to cross the membranes, we cannot exclude that its radical‐scavenging and antioxidant abilities can be important, also in our model, to justify the observed anti‐inflammatory activities.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the local physiological role of melatonin at the GIT is poorly characterized. In recent years, several in vivo studies showed that melatonin, administered intraperitoneally at high dose, has anti‐inflammatory effects in models of intestinal bowel disease (IBD) . This protection is mainly related with the prevention of nitro‐oxidative stress as well as with the reduction of inflammatory cell infiltration.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that nimesulide prevented the increase of oxidants, decrease of antioxidants and histopathologic damage by MTX in the intestinal tissue. Kolli et al demonstrated that higher dose of MTX then we used led to oxidative mucosal damage in the rat small intestines [14]. However, it was also reported that even lower doses of MTX (2.5 mg/kg) leads to marked oxidative damage in rat small intestines [3].…”
Section: Discussionmentioning
confidence: 99%